Stigmatization and the Impacts for Indigenous People with HIV/AIDS: A Scoping Review - Suarnianti Suarnianti; Indah Restika BN; Suhartatik Suhartatik; Erna Kadrianti (Indonesian Journal of Global Health Research, 2024)
The global substantial evidence highlights that HIV/AIDS-related stigma is a barrier to HIV prevention programs, treatment, and support services. Overcoming stigma and discrimination is the main guiding principle in HIV prevention and control programs. Such overcoming is crucial, especially for indigenous people with HIV/AIDS because they are often marginalized. Based on this background, this scoping review aims to explore the HIV/AIDS stigma and its impact, especially experienced by indigenous people. : This scoping review was conducted from November 2022 to March 2023 by searching for manuscripts on PubMed, Science Direct, Cochrane Library, Wiley, Directory of Open Access Journals, ProQuest, GARUDA, and Gray Literature databases to identify HIV/AIDS stigma and its impact in indigenous people. Three reviewers independently screened the results. The extracted data were then mapped, categorized, and summarized. This study has identified that HIV/AIDS stigma in indigenous people includes curses, divine vengeance, and infectious diseases. Various impacts arising from stigmatization include concealment, discrimination, powerlessness, unequal life opportunities, and social rejection/isolation. Moreover, the stigma impacts the service system and health service providers. It is necessary to have a complex strategy supported by the involvement of health authorities, health workers, and indigenous communities to overcome the problems of HIV/AIDS stigma and to understand the culture of indigenous people to prevent and treat HIV/AIDS.